Lockouts Involving Replacement Workers: An Empirical Public Policy Analysis and Proposal to Balance Economic Weapons Under the NLRA - Michael H. LeRoy (Washington University Law Quarterly, 1996)
Section Il.A provides an overview of factors contributing to this competition, including the North American Free Trade Agreement ("NAFTA"), the General Agreement on Tariffs and Trade ("GATr"), deregulation of large industries, rapidly improving technology, and massive layoffs resulting from corporate restructuring. Section II.B discusses specific instances where employers who locked out workers appeared to benefit from these changes in their relevant labor markets. Section IlI.A reviews early lockout doctrines that permitted employers to use this weapon only defensively in order to protect themselves from injuries such as sabotage of their equipment or poor production by workers. Section III.B shows how the Supreme Court expanded the use of the lockout in its 1957 NLRB v. Truck Drivers Local Union No. 449 ("Buffalo Linen") decision, by permitting an employer in a multiemployer bargaining group to lock out its workers in aid of a fellow employer whose employees went on strike, even though the first employer was neither struck nor harmed financially by its workers. Section III.C analyzes how American Ship Building permitted a single employer, someone who was not part of a multiemployer bargaining group, and therefore was not subject to the potential of a whipsaw strike – to lock out workers to advantageously control the timing of a labor dispute. Brown Food Store, discussed in Section III.D, created the leading precedent for an employer in a multiemployer group to conduct a lockout and to continue operations with replacement workers. Section III.E examines the National Labor Relations Board's ("NLRB" or "Board") extension of this precedent, in Harter Equipment, Inc.,31 to an employer who negotiates as an individual (i.e., not as a member of a multiemployer bargaining group). Section III.F explores two important doctrinal developments that occurred after Harter Equipment, Inc. Section IV presents this study's research findings. Section V presents a public policy proposal to curtail the pernicious use of replacement lockouts.
Keywords: Strikebreakers